Transcranial direct-current stimulation induced in stroke patients with aphasia: a prospective experimental cohort study - Santos, Michele Devido; Gagliardi, Rubens José; Mac-Kay, Ana Paula Machado Goyano; Boggio, Paulo Sergio; Lianza, Roberta; Fregni, Felipe (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVE: Previous animal and human studies have shown that transcranial direct current stimulation can induce significant and lasting neuroplasticity and may improve language recovery in patients with aphasia. The objective of the study was to describe a cohort of patients with aphasia after stroke who were treated with transcranial direct current stimulation. DESIGN AND SETTING: Prospective cohort study developed in a public university hospital. METHODS: Nineteen patients with chronic aphasia received 10 transcranial direct current stimulation sessions lasting 20 minutes each on consecutive days, using a current of 2 mA. The anode was positioned over the supraorbital area and the cathode over the contralateral motor cortex. The following variables were analyzed before and after the 10 neuromodulation sessions: oral language comprehension, copying, dictation, reading, writing, naming and verbal fluency. RESULTS: There were no adverse effects in the study. We found statistically significant differences from before to after stimulation in relation to simple sentence comprehension (P = 0.034), naming (P = 0.041) and verbal fluency for names of animals (P = 0.038). Improved scores for performing these three tasks were seen after stimulation. CONCLUSIONS: We observed that excitability of the primary motor cortex through transcranial direct current stimulation was associated with effects on different aspects of language. This can contribute towards future testing in randomized controlled trials.